2012
DOI: 10.1021/ic300510x
|View full text |Cite
|
Sign up to set email alerts
|

Single-Crystal Structures, Optical Absorptions, and Electronic Distributions of Thorium Oxychalcogenides ThOQ (Q = S, Se, Te)

Abstract: The compounds ThOS, ThOSe, and ThOTe have been synthesized, and their structures have been determined by means of single-crystal X-ray diffraction methods. All three compounds adopt the PbFCl structure type in the tetragonal space group D(4h)(7) - P4/nmm. More precise crystallographic data have been obtained for ThOS and ThOSe, which had previously only been known from X-ray powder diffraction data. ThOS, ThOSe, and ThOTe are yellow-, orange-, and black-colored, respectively. From single-crystal optical absorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…The reaction product contained dark-red crystals of Ba 3 ThSe 3 (Se 2 ) 2 (Ba:Th:Se≈3:1:7), black columnar crystals of Sb 2 Se 3 [31] (Sb:Se≈2:3), red crystals of BaSe, copper-colored crystals of Th 2 Se 5 [10] (Th:Se≈2:5), and plate-shaped red crystals of ThOSe [32]. Crystals of Ba 3 ThSe 3 (Se 2 ) 2 were subsequently obtained from the stochiometric reaction of the elements using the same heating conditions.…”
Section: Synthesesmentioning
confidence: 99%
“…The reaction product contained dark-red crystals of Ba 3 ThSe 3 (Se 2 ) 2 (Ba:Th:Se≈3:1:7), black columnar crystals of Sb 2 Se 3 [31] (Sb:Se≈2:3), red crystals of BaSe, copper-colored crystals of Th 2 Se 5 [10] (Th:Se≈2:5), and plate-shaped red crystals of ThOSe [32]. Crystals of Ba 3 ThSe 3 (Se 2 ) 2 were subsequently obtained from the stochiometric reaction of the elements using the same heating conditions.…”
Section: Synthesesmentioning
confidence: 99%
“…The EDX study on black irregularly shaped crystals showed the presence of Ba 2 Ag 2 Se 2 (Se 2 ) (Ba:Ag:Se ≈ 1:2:2). Other secondary phases present in the reaction product were orange plates of ThOSe (Th:Se ≈ 1:1) 35 and red blocks of BaSe (Ba:Se ≈ 1:1). 36 The synthesis of single crystals of Ba 2 Ag 2 Se 2 (Se 2 ) was further carried out by the stoichiometric reaction of BaSe (40.1 mg, 1.85 mmol), Ag (20 mg, 1.85 mmol), and Se (14.6 mg, 1.85 mmol) powders in an evacuated carbon-coated fused-silica tube.…”
Section: ■ Experimental Methodsmentioning
confidence: 99%
“…The EDX study on black irregularly shaped crystals showed the presence of Ba 2 Ag 2 Se 2 (Se 2 ) (Ba:Ag:Se ≈ 1:2:2). Other secondary phases present in the reaction product were orange plates of ThOSe (Th:Se ≈ 1:1) and red blocks of BaSe (Ba:Se ≈ 1:1) …”
Section: Experimental Methodsmentioning
confidence: 99%
“…The exchange-correlation functional with generalized gradient approximation (GGA) of Perdew-Burke-Ernzerhof (PBE)40 was used to solve the Kohn-Sham equations with a kinetic energy cutoff of 600 eV. Since none of the localized 5f-like band is occupied in Th, the DFT with the GGA approximation was proved to be effective enough to describe the structural and vibrational properties of Th-based compounds11414243. The free energy global minimization of ThC 2 were performed by merging ab initio total energy calculations and particle-swarm optimization algorithm19 on structural predictions, as implemented in the CALYPSO code20.…”
Section: Methodsmentioning
confidence: 99%